Anatomical characterization of vagal nodose afferent innervation and ending morphologies at the murine heart using a transgenic approach - Kazcı, Yusuf Enes; Şahoğlu Göktaş, Sevilay; Aydın, Mehmet Şerif; Karadoğan, Behnaz; Nebol, Aylin; Turhan, Mehmet Uğurcan; Öztürk, Gürkan; Çağavi, Esra (Elsevier B.V., 2022)
Heart is an extensively innervated organ and its function is strictly coordinated by autonomic neural circuits. After pathological events such as myocardial infarction (MI), cardiac nerves undergo a structural and functional remodeling contributing to cardiac dysfunction. Although the efferent component of the cardiac nerves has been well described, sensory innervation of the heart has not been defined in detail. Considering its importance, comprehensive description of vagal afferent innervation on the whole heart would enable a better description of autonomic imbalances manifesting as sympathoexcitation and vagal withdrawal in post-ischemic states. To address this issue, we globally mapped the vagal nodose afferent fibers innervating the whole murine heart with unprecedented resolution. By using the Phox2b-Cre
Keywords: Heart; Myocardial Infarct; Neural Remodeling; Nodose Ganglia; Vagal Afferents; Whole Organ Imaging